2017
DOI: 10.37236/6362
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for Distinguishing Invariants of Infinite Graphs

Abstract: We consider infinite graphs. The distinguishing number D(G) of a graph G is the minimum number of colours in a vertex colouring of G that is preserved only by the trivial automorphism. An analogous invariant for edge colourings is called the distinguishing index, denoted by D (G). We prove that D (G) D(G) + 1. For proper colourings, we study relevant invariants called the distinguishing chromatic number χ D (G), and the distinguishing chromatic index χ D (G), for vertex and edge colourings, respectively. We sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In [15] the chromatic distinguishing number of infinite graphs is investigated. For connected graphs of bounded valence d it is shown that χ D (G) 2d − 1, and for infinite subcubic graphs of infinite motion this improves to χ D (G) 4.…”
Section: Higher Valence Can We Classify Graphs G With D = D(g)?mentioning
confidence: 99%
“…In [15] the chromatic distinguishing number of infinite graphs is investigated. For connected graphs of bounded valence d it is shown that χ D (G) 2d − 1, and for infinite subcubic graphs of infinite motion this improves to χ D (G) 4.…”
Section: Higher Valence Can We Classify Graphs G With D = D(g)?mentioning
confidence: 99%
“…We will define two analogs of a proper coloring, each of which leads to a distinguishing chromatic number. The analogous parameter for graphs, χ D (G), is introduced in [8] and studied further by other authors, see for example [3,4,7,10]. Definition 23.…”
Section: Distinguishing Chromatic Numbermentioning
confidence: 99%
“…The distinguishing index D (G) of a graph G is the smallest number of colours such that there is an edge colouring which is not preserved by any non-identity automorphism. Many results about distinguishing numbers hold for distinguishing indices as well, sometimes with almost identical proofs (see [3,8,9], for example). Furthermore, there are problems such as Tucker's Infinite Motion Conjecture [12] that are still wide open for vertex colourings, but whose edge colouring version has a relatively simple proof [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was first proved for finite graphs in [9]. See [8] for an extension to infinite graphs and [10] for an alternative proof for both finite and infinite graphs. It was shown in [8] that Theorem 1.1 remains true even if D(G) is an arbitrary infinite cardinal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation